Endocytosis of GABA(C) receptors depends on subunit composition and is regulated by protein kinase C-? and protein phosphatase 1 - Linck, Lisa; Binder, Jasmin; Haynl, Christian; Enz, Ralf (Journal of Neurochemistry, 2015)
Neuronal excitability depends on the surface concentration of neurotransmitter receptors. Type C gamma-aminobutyric acid receptors (GABA(C)R) are composed of ? subunits that are highly expressed in the retina. Molecular mechanisms that guide the surface concentration of this receptor type are largely unknown. Previously, we reported physical interactions of GABA(C)R ? subunits with protein kinase C-? (PKC?) via adapter proteins of the ZIP protein family, as well as of protein phosphatase 1 (PP1) via PNUTS. Here, we demonstrate that co-expressing ?1 with ZIP3 and PKC? enhanced basal internalization of GABA(C)R, while receptor internalization was reduced in the presence of PNUTS and PP1. Co-expression of ?1 with individual binding partners showed no alterations, except for PP1. Heterooligomeric GABA(C)R composed of ?1 and ?2 subunits had a significant higher endocytosis rate than ?1 containing homooligomeric receptors. Mutant constructs lacking binding sites for protein interactions ensured the specificity of our data. Finally, substitution of serine and threonine residues with alanines indicated that GABA(C)R internalization depends on serine/threonine kinases and phosphatases, but not on tyrosine phosphorylation. We conclude that GABA(C)R internalization is reciprocally regulated by PKC? and PP1 that are anchored to the receptor via ZIP3 or PNUTS respectively.
EVALuna2:4723

Exploration of Sulfur Assimilation of Aspergillus fumigatus Reveals Biosynthesis of Sulfur-Containing Amino Acids as a Virulence Determinant - Amich, Jorge; Duemig, Michaela; O'Keeffe, Grainne; Binder, Jasmin; Doyle, Sean; Beilhack, Andreas; Krappmann, Sven (Infection and Immunity, 2016)
Fungal infections are of major relevance due to the increased numbers of immunocompromised patients, frequently delayed diagnosis, and limited therapeutics. To date, the growth and nutritional requirements of fungi during infection, which are relevant for invasion of the host, are poorly understood. This is particularly true for invasive pulmonary aspergillosis, as so far, sources of (macro)elements that are exploited during infection have been identified to only a limited extent. Here, we have investigated sulfur (S) utilization by the human-pathogenic mold Aspergillus fumigatus during invasive growth. Our data reveal that inorganic S compounds or taurine is unlikely to serve as an S source during invasive pulmonary aspergillosis since a sulfate transporter mutant strain and a sulfite reductase mutant strain are fully virulent. In contrast, the S-containing amino acid cysteine is limiting for fungal growth, as proven by the reduced virulence of a cysteine auxotroph. Moreover, phenotypic characterization of this strain further revealed the robustness of the subordinate glutathione redox system. Interestingly, we demonstrate that methionine synthase is essential for A. fumigatus virulence, defining the biosynthetic route of this proteinogenic amino acid as a potential antifungal target. In conclusion, we provide novel insights into the nutritional requirements ofA. fumigatus during pathogenesis, a prerequisite to understanding and fighting infection.
EVALuna2:7707

Impairing fluoride export of Aspergillus fumigatus mitigates its voriconazole resistance - Binder, Jasmin; Held, Jürgen; Krappmann, Sven (International Journal of Antimicrobial Agents, 2019)
Fungi have evolved specific export activities to balance intracellular levels of the toxic ion fluoride, while the first-line antimycotic voriconazole contains fluorine. This study aimed to explore whether impaired fluoride export might result in altered susceptibilities of the human pathogenic mould Aspergillus fumigatus towards this antifungal compound. Functional characterization of the putative fluoride exporter in A. fumigatus was performed in the context of azole resistance by generating deletion strains that were assessed for their resistance against fluoride and voriconazole. The FexA fluoride exporter of A. fumigatus appears to be expressed constitutively, and targeting its encoding gene results in significantly increased sensitivity towards this halide. Impaired fluoride export correlates with increased susceptibility of an azole-resistant fexAΔ strain. These results demonstrate that the fexA-encoded gene product is the major fluoride export activity of A. fumigatus, and that voriconazole serves as a source of fluoride. However, these data do not support the application of voriconazole based on fluoride toxicity.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Aspergillosis; Azole resistance; FEX

Mutant characterization and in vivo conditional repression identify aromatic amino acid biosynthesis to be essential for Aspergillus fumigatus virulence - Sasse, Anna; Hamer, Stefanie N.; Amich, Jorge; Binder, Jasmin; Krappmann, Sven (Virulence, 2016)
Pathogenicity of the saprobe Aspergillus fumigatus strictly depends on nutrient acquisition during infection, as fungal growth determines colonisation and invasion of a susceptible host. Primary metabolism has to be considered as a valid target for antimycotic therapy, based on the fact that several fungal anabolic pathways are not conserved in higher eukaryotes. To test whether fungal proliferation during invasive aspergillosis relies on endogenous biosynthesis of aromatic amino acids, defined auxotrophic mutants of A. fumigatus were generated and assessed for their infectious capacities in neutropenic mice and found to be strongly attenuated in virulence. Moreover, essentiality of the complete biosynthetic pathway could be demonstrated, corroborated by conditional gene expression in infected animals and inhibitor studies. This brief report not only validates the aromatic amino acid biosynthesis pathway of A. fumigatus to be a promising antifungal target but furthermore demonstrates feasibility of conditional gene expression in a murine infection model of aspergillosis.
EVALuna2:7691

The Essential Thioredoxin Reductase of the Human Pathogenic Mold Aspergillus fumigatus Is a Promising Antifungal Target - Binder, Jasmin; Shadkchan, Yana; Osherov, Nir; Krappmann, Sven (Frontiers in Microbiology, 2020)
The identification of cellular targets for antifungal compounds is a cornerstone for the development of novel antimycotics, for which a significant need exists due to increasing numbers of susceptible patients, emerging pathogens, and evolving resistance. For the human pathogenic mold Aspergillus fumigatus, the causative agent of the opportunistic disease aspergillosis, only a limited number of established targets and corresponding drugs are available. Among several targets that were postulated from a variety of experimental approaches, the conserved thioredoxin reductase (TrxR) activity encoded by the trxR gene was assessed in this study. Its essentiality could be confirmed following a conditional TetOFF promoter replacement strategy. Relevance of the trxR gene product for oxidative stress resistance was revealed and, most importantly, its requirement for full virulence of A. fumigatus in two different models of infection resembling invasive aspergillosis. Our findings complement the idea of targeting the reductase component of the fungal thioredoxin system for antifungal therapy.
CRIS-Team Scopus Importer:2020-07-24
Keywords: aspergillosis; conditional promoter replacement; essentiality; TetOFF; thioredoxin

The infectious propagules of Aspergillus fumigatus are coated with antimicrobial peptides - Dümig, Michaela; Binder, Jasmin; Gaculenko, Anastasia; Daul, Franziska; Winandy, Lex; Hasenberg, Mike; Gunzer, Matthias; Fischer, Reinhard; Künzler, Markus; Krappmann, Sven (Cellular Microbiology, 2021)
Fungal spores are unique cells that mediate dispersal and survival in the environment. For pathogenic fungi encountering a susceptible host, these specialised structures may serve as infectious particles. The main causative agent of the opportunistic disease aspergillosis, Aspergillus fumigatus, produces asexual spores, the conidia, that become dissipated by air flows or water currents but also serve as propagules to infect a susceptible host. We demonstrate that the defX gene of this mould encodes putative antimicrobial peptides resembling cysteine-stabilised (CS)αβ defensins that are expressed in a specific spatial and temporal manner in the course of asexual spore formation. Localisation studies on strains expressing a fluorescent proxy or tagged defX alleles expose that these antimicrobial peptides are secreted to coat the conidial surface. Deletion mutants reveal that the spore-associated defX gene products delay the growth of Gram-positive Staphylococcus aureus and demonstrate that the defX gene and presumably its encoded spore-associated defensins confer a growth advantage to the fungal opponent over bacterial competitors. These findings have implications with respect to the ecological niche of A. fumigatus that serves as a ‘virulence school’ for this human pathogenic mould; further relevance is given for the infectious process resulting in aspergillosis, considering competition with the host microbiome or co-infecting microorganisms to break colonisation resistance at host surfaces.
CRIS-Team Scopus Importer:2021-03-12
Keywords: aspergillosis; defensin-like peptide; fungal virulence